Association between dental age and malocclusions: a systematic review - Gabriela Fonseca-Souza; Amanda Renostro-Souza; Lhorrany Alves-Souza; Geraldo Thedei Junior; Maria Angélica Hueb de Menezes-Oliveira; Lívia Azeredo Alves Antunes; Svenja Beisel-Memmert; Christian Kirschneck; Juliana Feltrin-Souza; Erika Calvano Küchler (BMC, 2024)
Abstract Background The evidence in the literature suggests that some skeletal or dental malocclusions are involved with dental development, resulting in advanced or delayed dental age (DA). The purpose of this systematic review was to investigate the association between DA and different types of malocclusions. Methods The search was carried out on PubMed, Scopus, Web of Science, Virtual Health Library, and in the gray literature. Observational studies that evaluated the association between DA and sagittal, vertical, or transversal malocclusions were included. The quality assessment was performed using the Newcastle-Ottawa Scale (NOS). The data from primary studies were narratively synthesized. The certainty of evidence was evaluated using the GRADE approach. The study was conducted from August 2023 to October 2023. Results One Thousand Nine Hundred Ninety-One records were identified in the initial search. Twenty (n = 20) studies were included. Most of the studies (n=15) presented a moderate quality according to NOS. Twelve studies evaluated the association between DA and sagittal discrepancies; eight studies evaluated vertical discrepancies, and only one study analyzed a transversal discrepancy. Demirjian's method for DA assessment was the most used among the studies. The primary studies observed that patients of both sexes presenting a vertical growth pattern and males with skeletal Class III malocclusion tend to have advanced DA. The study that investigated transversal malocclusion found that unilateral posterior cross-bite is associated with delayed DA. The certainty of evidence was very low for all outcomes evaluated. Conclusion DA may be associated with the type of malocclusion. It is suggested that DA can be used as an initial diagnostic tool in orthodontics. Future well-designed studies should be performed in order to investigate the association between DA and different types of malocclusions in more detail. Trial registration This study was registered in the PROSPERO database (CRD42023454207).